Same song, new dance: analyzing market structure and competition in the digital music aggregation industry - Kaye, D. Bondy Valdovinos (Kansas State University, 2016)
Technological revolutions of the past century have fueled dynamic paradigm shifts across a broad spectrum of mass media industries. This study examines an innovative new market segment in the music recording industry: digital music aggregation. Digital music aggregators are music distributors that directly connect artists, any creator of musical content, to digital music vendors, online music stores such as iTunes or digital music streaming services such as Spotify. Digital music aggregator companies offer services similar to major record labels, such as mass distribution, royalty collection, and intellectual property protection. Digital music aggregators provide services to artists at all levels of prestige and experience. Essentially any artist interested in publishing music can do so using digital music aggregators. Despite their growing influence in the music recording industry, digital music aggregators have been afforded little scholarly attention. This study responds to Galuszka's (2015) call for further research on aggregator market structure and competition, proposing the following research questions: 1) how is the digital music aggregator market structured? 2) What competitive strategies do digital music aggregators employ? This study is framed by the industrial organizational model of market structure (Bain, 1968) and Porter’s (1980) theories of competitive strategy. Six in-depth qualitative interviews were conducted for this study. Results illuminate market structure and competitive strategies in the digital music aggregation industry and lay foundation for future study and industrial application within this nascent branch of the music recording industry.
Keywords: Music industry; Aggregator; Market structure; Competition